2011
DOI: 10.1638/2011-0112.1
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Biochemistry Values of Recently Wild-Caught Purple Mouth Moray Eels (Gymnothorax vicinus)

Abstract: The primary purpose of this study was to establish plasma biochemistry parameters for healthy recently wild-caught purple mouth moray eels (Gymnothorax vicinus) to provide a baseline of data for improved medical care in an aquarium or zoologic setting and for wild health assessments. Thirty-one clinically healthy purple mouth moray eels of unknown age and sex were caught from the wild, and were anesthetized 50 days following capture for blood collection from the ventral coccygeal vein. The median plasma bioche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…Only three studies measured blood plasma [Cl − ], but none of them found significant changes after exposure to OA-like conditions Green and Jutfelt, 2014;Heinrich et al, 2014). The lack of change in plasma [Cl − ] in marine fish could be due to the difficulty in accurately measuring small changes in [Cl − ] compared with 'background' control levels of 140-200 mmol l −1 (see Genz et al, 2008;Erlacher-Reid et al, 2011;Esbaugh et al, 2016;Lin et al, 2003;Toews et al, 1983;reviewed in Evans et al, 2005). However, it is also possible that the large range of reported values of [Cl − ] reflect species-, life stage-or metabolism-specific differences.…”
Section: Pharmacological Considerationsmentioning
confidence: 99%
“…Only three studies measured blood plasma [Cl − ], but none of them found significant changes after exposure to OA-like conditions Green and Jutfelt, 2014;Heinrich et al, 2014). The lack of change in plasma [Cl − ] in marine fish could be due to the difficulty in accurately measuring small changes in [Cl − ] compared with 'background' control levels of 140-200 mmol l −1 (see Genz et al, 2008;Erlacher-Reid et al, 2011;Esbaugh et al, 2016;Lin et al, 2003;Toews et al, 1983;reviewed in Evans et al, 2005). However, it is also possible that the large range of reported values of [Cl − ] reflect species-, life stage-or metabolism-specific differences.…”
Section: Pharmacological Considerationsmentioning
confidence: 99%
“…The animal was positioned in left lateral recumbency on the cart and was ventilated by placing a rubber tube in the mouth such that water flowed continuously over the gills. Blood was collected from the ventral coccygeal vein, processed, and stored according to methods previously utilized for morays (Erlacher-Reid et al 2011) and recommended for teleost fish (Groff and Zinkl 1999). Plasma was temporarily stored at −20 • C, and biochemistry analytes were measured within 1-5 d of collection.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma triglyceride and cholesterol values, including high-density and low-density lipoprotein concentrations, in the male California moray at 6, 12, and 16 months after dietary changes were implemented (i.e., Atlantic herring were removed from its diet, and feeding frequency was decreased from three to two times per week). and aquarium-maintained purplemouth morays G. vicinus and green morays G. funebris (Erlacher-Reid et al 2011;Clode et al, in press). The plasma triglyceride value (2,023 mg/dL) for this California moray was also markedly higher than those of the wild-caught morays but was similar to values reported for many of the aquarium-maintained morays (Erlacher-Reid et al 2011;Clode et al, in press).…”
Section: Clinical Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Blood was collected (3 mL, Table 1) in a heparinized syringe for a complete blood count and plasma chemistry, which were considered normal (Francis-Floyd et al 1991;Erlacher-Reid et al 2011).…”
mentioning
confidence: 99%